Rejustifying Retributive Punishment on Utilitarian Grounds in Light of Neuroscientific Discoveries more than Philosophical Calisthenics! - McCaleb, Robert B. (2015)
Each of these unique features [of the Rotten Social Background (RSB) defense] is skeptically received by the classical criminal law mainly because of its fundamentally non-scientific, folk-psychological position on free will. However, discoveries in contemporary neuroscience strongly support each of these features. While chemical, causal, and deterministic brain events indisputably play a central role, RSB is virtually ignored as a frightening intrusion by materialism into the dualist sanctuary of the law. Yet RSB, as an indicator species for the health of the criminal law’s philosophic ecosystem, cannot be discounted out of hand any longer. In fact, the reconciliation of law and materialism is both practically and morally obligatory. This note proposes that such a reconciliation might be best accomplished by rebuilding the otherwise discredited retributive justifications of punishment on essentially utilitarian foundations, an idea discussed extensively below at section C of the Discussion. Merely re-explaining the theoretical underpinnings of retributive punishment without proposing practical changes would amount to a demonstration of linguistic calisthenics. Therefore, in conjunction with a theoretical reappraisal, there must also be several practical modifications to traditional retributive “punishment” that may serve to maximize the utility of a re-justified utilitarian retributivism. However, these expansions are beyond the scope of this note. Rather, the main practical focus will be on crafting a model statute—in the style of the American Legal Institute’s Model Penal Code—that brings the aery language of Bazelon’s dissent into a more concrete form